Concerning the scientific reformulation of probability in the work of Antoine. A. Cournot - Gómez, Andrea Vergara (Re-presentaciones: Periodismo, comunicación y sociedad, 2021)
Probability is one of the most characteristic scientific concepts in modeling processes for natural and social phenomena in the last two centuries, especially due to the awareness that is acquired regarding the omnipresence of randomness. However, the epistemic discussion around the meanings of probability dates back to the 19th century. In order to vindicate one of the meanings of probability typical of this time, a historical-epistemological study of the work Exposition de la théorie des chances et des probabilités (1843) by Antoine Augustin Cournot is made. The analysis will identify a dual conceptualization of probability as an onto-epistemic unit, which legitimizes its objective and subjective nature at the same time. This notion allows us to reconsider the fragmented view that exists today about the mathematical meanings of probability.